The Role of Work-Life Balance, Work Flexibility, and Career Development in Increasing Job Satisfaction of Generation Z Employees - Deviana Nurul Sholekha; Raniasari Bimanti Esthi (International Journal of Economics and Management Research, 2025)
Generation Z students enrolled in the weekend regular program at Pelita Bangsa University often face challenges in maintaining a proper work-life balance due to the dual burden of studying and working. This generation has unique expectations related to work flexibility and career development opportunities. However, these expectations are frequently constrained by limited institutional facilities and support systems, which can negatively impact their job satisfaction. This study aims to analyze the role of work-life balance, work flexibility, and career development in improving job satisfaction among Generation Z employees. A quantitative research method was employed, utilizing the IBM SPSS 29.0.0.0 application for data analysis. Data were collected through a combination of observation, literature review, and the distribution of questionnaires to 38 students from Pelita Bangsa University’s Agribusiness weekend program who also work while studying. The results of the study indicate that work-life balance has a significant influence on job satisfaction, with a p-value of less than 0.001, showing a strong correlation. Work flexibility also contributes significantly, with a p-value of 0.002, and career development is likewise significant with a p-value of less than 0.001. These findings suggest that each of the three independent variables—work-life balance, work flexibility, and career development—has a statistically significant and positive effect on job satisfaction, both partially and simultaneously.In conclusion, Generation Z employees benefit significantly from balanced work and study environments, adaptable work arrangements, and clear opportunities for career progression. Organizations and academic institutions should collaborate to provide greater support and resources to help this generation meet their educational and professional goals. By addressing these factors, job satisfaction among Generation Z workers can be improved, leading to better performance, motivation, and overall well-being.